THE IMPORTANCE OF BALANCE THEORIES IN THE FORMATION OF FINANCIAL RESULTS - A. Avlokulov (International Journal of Psychosocial Rehabilitation, 2020)
This article provides a comparative analysis of the requirements of existing balance theories in the preparation of financial statements. As a result of the research, the effectiveness of organic balance in the formation of financial results by businesses at the level of requirements of international standards is substantiated.